PENGARUH KARAKTER EKSEKUTIF, TRANSFER PRICING DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Faudzan, Ryo Tegar; Widiyati, Dian (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The purpose of this study is to analyse the effect of executive character, transfer pricing and sales growth on tax avoidance. The independent variables used are executive character, transfer pricing and sales growth. The dependent variable used is tax avoidance. The population in this study are properties and real estate companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. The sampling method used was purposive sampling with a sample of 28 companies. The analysis method used in this research is multiple linear regression which is processed using the Eviews 9 application. The data source for this research is the Financial Statements. The result of partial research  show that executive character affects tax avoidance, while transfer pricing and sales growth have no effect on tax avoidance. The result of this study simultaneously show that executive character, transfer pricing, and sales growth have an influence on tax avoidance.